Renee Hirschon, Heirs of the Greek Catastrophe: The social Life of Asia Minor Refugees in Piraeus - Allen, Peter S. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1988)
[ Δε διατίθεται περίληψη / no abstract available]